Bacterial Enzymes Associated With Gastropod Mollusc Nacella concinna From the Water Area of the Argentine Islands (West Antarctica) - Berezkina , Anna; Avdiuk , Kateryna; Gudzenko , Olena; Maksim A. Kharkhota , Maksim A. Kharkhota; Utevsky , Andriy (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 295